Analisis profitabilitas pada perusahaan pertambangan batubara yang terdaftar di bursa efek Indonesia - Muhammad Nurron; Dhani Ichsanuddin Nur (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2022)
Indonesia is a developing country that has abundant natural resources potential, one of which is coal mining which is one of Indonesia's leading commodities, one of the efforts to achieve the goal of coal mining companies is always trying to maximize profits. Many factors can affect a company's profitability level. This study aims to analyze the influence of variable liquidity, company size, sales growth, and debt to asset ratio on the profitability of manufacturing companies in Indonesia.The population of this study is coal mining sub-sector companies registered in IDX in 2014 – 2018. The sample was taken using purposive sampling method so that 20 companies qualified as samples were obtained. This study uses regression analysis method to determine the influence of free variables consisting of liquidity, company size, sales growth, debt to asset ratio to profitability (ROA) of the company.The results showed that variable liquidity and also the size of the company contributed to the profitability of the company, while sales growth and also debt to asset ratio did not contribute to the profitability of coal mining companies.